2018
DOI: 10.1101/454843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic evolutionary history and gene content of sex chromosomes across diverse songbirds

Abstract: 29Songbirds have a species number almost equivalent to that of mammals, and are classic 30 models for studying mechanisms of speciation and sexual selection. Sex chromosomes are 31 hotspots of both processes, yet their evolutionary history in songbirds remains unclear. To 32 elucidate that, we characterize female genomes of 11 songbird species having ZW sex 33 chromosomes, with 5 genomes of bird-of-paradise species newly produced in this work. We 34 conclude that songbird sex chromosomes have undergone at leas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 79 publications
5
42
1
Order By: Relevance
“…The genes involved in the such cases 149 nevertheless have probably already become pseudogenes. Our results are in line with the 150 reported cases in avian W or mammalian Y chromosomes that dosage-sensitive genes are 151 retarded for their functional degeneration due to the strong selective constraints (Bellott,et al 152 2014; Smeds, et al 2015;Bellott, et al 2017;Xu, et al 2019). We also provided new evidence 153 that sex-specific selection is shaping the evolution of the W chromosome, which was assumed 154 to be less frequent than that shaping the Y chromosome, due to the more frequent and intensive 155 male-targeted sexual selection.…”
Section: Transpositions 136supporting
confidence: 87%
See 1 more Smart Citation
“…The genes involved in the such cases 149 nevertheless have probably already become pseudogenes. Our results are in line with the 150 reported cases in avian W or mammalian Y chromosomes that dosage-sensitive genes are 151 retarded for their functional degeneration due to the strong selective constraints (Bellott,et al 152 2014; Smeds, et al 2015;Bellott, et al 2017;Xu, et al 2019). We also provided new evidence 153 that sex-specific selection is shaping the evolution of the W chromosome, which was assumed 154 to be less frequent than that shaping the Y chromosome, due to the more frequent and intensive 155 male-targeted sexual selection.…”
Section: Transpositions 136supporting
confidence: 87%
“…Some 43 genes with important regulatory functions or high dosage-sensitivity have been demonstrated to 44 be degenerating much slower than others on the mammalian Y (Bellott, et al 2014;Cortez, et 45 al. 2014) or avian W chromosomes (Smeds, et al 2015;Bellott, et al 2017;Xu, et al 2019) due 46 to a much higher level of selective constraints. The human Y chromosome has evolved 47 palindromic sequence structures to repair deleterious mutations and facilitate gene conversions 48 between Y-linked genes (Rozen, et al 2003).…”
mentioning
confidence: 99%
“…And studies in fungi species Microbotryum lychnidis-dioicae 61 and Neurospora tetrasperma 62 indicated that patterns of evolutionary strata can form without sexual antagonism or chromosome inversions. We have previously reported that the youngest evolutionary stratum of songbirds has probably formed due to the lineage-specific burst of TEs 63 . In this work, we provided clear evidence that the youngest evolutionary stratum of Chilean tinamou formed without chromosome inversions between Z and W chromosomes (Figure 3).…”
Section: Discussionmentioning
confidence: 98%
“…Retention of divergent Wlinked gametologs could appear consistent with incomplete dosage compensation, if the reads arising from the W-linked copy no longer map to the Z-linked copy and are thus invisible in the absence of a W assembly. However, previous work in birds suggest that only a very small fraction of Z-linked genes in the DR retain W gametologs Xu et al 2019), making this explanation unlikely to account for the bulk of expression differences between sexes in the DR.…”
Section: Genes With Male-biased Expression Are Not Overrepresented Inmentioning
confidence: 90%
“…Theoretical models predict that suppression of recombination will be favored so that the sexually antagonistic alleles that are beneficial in the heterogametic sex can be linked genetically to the sex determination locus (Rice 1987;Ellegren 2011). Recombination suppression leads to the formation of evolutionary strata, which can occur multiple times in the course of sex chromosome evolution (Lahn and Page 1999;Bergero and Charlesworth 2009;Cortez et al 2014;Zhou et al 2014;Wright et al 2016;Xu et al 2019). Despite differences in their autosomal origins and heterogamety, eutherian mammals and neognathous birds followed similar but independent trajectories of sex chromosome evolution (Graves 2015;Bellott et al 2017).…”
Section: Introductionmentioning
confidence: 99%